2019
DOI: 10.3389/fimmu.2019.00376
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Lupus Anticoagulant and Anti-phosphatidylserine/prothrombin Autoantibodies in Antiphospholipid Syndrome: A Multicenter Study

Abstract: Background: Is it well-known that one of the major drawbacks of Lupus Anticoagulant (LA) test is their sensitivity to anticoagulant therapy, due to the coagulation based principle. In this study we aimed to assess the reproducibility of LA testing and to evaluate the performance of solid assay phosphatidylserine/prothrombin (aPS/PT) antibodies.Methods: We included 60 patients that fulfilled the following inclusion criteria: (I) diagnosis of thrombotic antiphospholipid syndrome (APS); (II) patients with thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…This approach is particularly important when it comes to the identification of a novel biomarker to diagnose seronegative APS patients. 24,56,57 A final comment goes to the potential clinical significance of our findings. Because of their different mechanism of prothrombin binding, type I and II Abs might have different origin and pathologic effects.…”
Section: Discussionmentioning
confidence: 90%
“…This approach is particularly important when it comes to the identification of a novel biomarker to diagnose seronegative APS patients. 24,56,57 A final comment goes to the potential clinical significance of our findings. Because of their different mechanism of prothrombin binding, type I and II Abs might have different origin and pathologic effects.…”
Section: Discussionmentioning
confidence: 90%
“…Anti-phosphatidylserine/prothrombin antibodies (aPS/ PT) are now acknowledged as a highly effective potential marker for APS [10,11]. As a result of its remarkable diagnostic performance and high prevalence in the LA-positive patient group, as validated by multiple studies [12][13][14], aPS/PT has gained much attention and was included in both the APS-S (Otomo) and the Global APS Score (GAPSS), widely used systems for patient thrombotic risk assessment [15]. Additional biomarkers continue to be evaluated for their value to APS diagnosis and management.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although several studies have suggested that testing for "extra criteria" aPL specificities may help to identify patients at higher risk for developing clinical manifestations of the syndrome, their role in LO-PC needs further investigation. 9,10 In particular, IgA isotypes, phosphatidylserine-prothrombin antibodies (aPS/PT) and β2GPI-Domain 1 (β2GPI-D1) have been proposed to be particularly relevant in the antiphospholipid syndrome setting, but their relevance in the specific context of pregnancy needs to be confirmed. [11][12][13] Our study aimed to investigate the prevalence of aPL antibodies, both "criteria" and "extra criteria," in a cohort of women who experienced LO-PC with low risk for chromosomal abnormalities.…”
Section: Introductionmentioning
confidence: 99%